Teachers’ Understanding and Application of Algebra Learning at the Kindergarten in Group B - Astuti, Febru Puji (Prosiding University Research Colloquium, 2021)
Early childhood education institutions are expected to provide optimal opportunities for children to access mathematical ideas and concepts include algebra. Existing research shows the challenges in learning mathematics for children, especially algebra, one of which is the competence of educators related to mastery skills and knowledge of the material in teaching. This research uses a survey research type by using a questionnaire as a data collection tool. Questionnaires are used to obtain data related to a brief description of the understanding and application of teacher algebra learning at the Kindergarten level group B. The findings from a sample of 33 respondents reported; 1) educators’ self-understanding about algebra learning, 42% of respondents are still not sure what algebraic material coverage needs to be taught, 39% of respondents stated that they know the scope of algebraic material that needs to be taught. 2) Teachers’ teaching skills and abilities, 45% of respondents are able and frequently teach algebra material even though the practice does not cover all materials.